The Commodification of Islamic Symbols for The Development of Halal Tourism - Andy Hakim; Rizka Ar Rahmah; Ahmad Salman Farid (IJIBE (International Journal of Islamic Business Ethics), 2025)
This study examines the challenges and opportunities of developing halal tourism in Lake Toba, Indonesia, and provides recommendations to improve policies and facilities to better accommodate Muslim travellers. A qualitative case study approach was employed, focusing on Lake Toba as the research setting. Data were collected through in-depth interviews with key stakeholders, including government officials, tourism industry actors, and Muslim tourists, as well as through direct field observations. Thematic analysis was used to identify key issues and development potentials related to halal tourism. The findings reveal that although most visitors to Lake Toba are Muslim, there is a significant lack of halal tourism facilities, including halal-certified restaurants, sharia-compliant accommodations, and halal slaughterhouses. Policy inconsistencies between local governments also hinder coherent halal tourism development. Nonetheless, support from institutions such as BPODT and the Simalungun Tourism Office demonstrates promising potential for improvement. Social resistance, political complexity, and infrastructure gaps remain key challenges. The study highlights the need for enhanced halal facilities, harmonized interregional policies, and community education on the benefits of halal tourism. Strengthened coordination between government bodies and the private sector is essential for sustainable development. This research provides new insights into halal tourism development in a multicultural, predominantly non-Muslim area, emphasizing the importance of stakeholder collaboration, policy alignment, and sociocultural sensitivity.